CNS tuberculoma in an immunocompetent patient: A case report of multi-drug hypersensitivity to RIPE therapy - Benjamin Huber; Seema Joshi (IDCases, 2023)
Background: Tuberculosis (TB) is the second leading cause of death due to an infectious disease worldwide (World Health Organization, 2022 [1]). The first line treatment of TB involves the concurrent use of four drugs: rifampin, isoniazid, pyrazinamide, and ethambutol (RIPE). Given the rising threat of multidrug resistant TB, it is crucial to understand how TB can be treated when first line treatment is not an option. Case presentation: We report a rare case of multi-drug hypersensitivity to RIPE therapy in an immunocompetent patient with an unusual presentation of CNS tuberculoma. The patient presented to an outside hospital four months prior with weakness, numbness, imbalance, and speech difficulties. A CT of the head revealed a mass in the left parietal lobe that demonstrated chronic necrotizing granulomatous inflammation with positive cultures for M. tuberculosis. The patient was started on a regimen of rifampin 600 mg daily, isoniazid 300 mg daily, pyrazinamide 2000 mg daily, ethambutol 1200 mg daily, and pyridoxine 50 mg daily. However, the patient developed drug hypersensitivity reactions to both rifampin and ethambutol with subsequent failed desensitization to rifabutin. She was ultimately discharged from the hospital on a regimen of isoniazid, pyridoxine, pyrazinamide, and moxifloxacin with plans for outpatient follow-up. Conclusions: This case highlights a rare clinical presentation of multiple drug hypersensitivity in the setting of a CNS tuberculoma and the importance of identifying the offending agents early in the course of treatment and adjusting the drug regimen accordingly. Desensitization should be attempted, but if ineffective, then alternative drug regimens should be formulated on a case-by-case basis.